Toronto's Portuguese-speaking community potential for creating a social support-networks for breast cancer - Christine Maheu; Margareth Santos Zanchetta; Abinet Gebreegziabher Gebremariam; Mary Rachel Lam- (Universidade Federal de Goias, 2020)
An ethnographic study explored ideas about the possibility of creating social support networks for breast cancer within the Portuguese-speaking community in Toronto (Canada). Nineteen men and women from Angolan, Brazilian and Portuguese communities informed about a social support network with a focus on enabling versus challenging conditions for its construction. The fundamental components in creating social support networks were: the demystification of breast cancer and its prevention, emphasis on health education, mobilizing volunteers and direct social support to women living with breast cancer. The potential enabling factors were the participation of older women as social leaders, and the utilization of schools and religious institutions. Perceived barriers were: breast cancer believed to be women's disease, lack of knowledge about its cure/ rehabilitation, as well as a limited sensitivity to cancer. Social support networks should consider the communities' diverse cultural and tangible needs, as well as more informal social support services.